Reinventing the branch: An empirical assessment of banking strategies to environmental differentiation - ALLARD, Thomas (Institutional Knowledge at Singapore Management University, 2009)
The present study investigates the effects of two atmospheric differentiation strategies currently used by banks: co-locating with a hedonic business vs. refurbishing through an upscale environment. We assessed the potential moderating effects of congruency between the retail environment and the type of services. Using a Structural Equation Model based on 300 bank visit intercepts, we found significant differences between modern branch concepts and the traditional one in their influence on customers’ retail experience. More specifically, the type of atmospheric strategy moderates the relationship between retail environment and customers’ affect and the relationship between affect and approach behavior. Also, the mediating role of the employees and financial services evaluation varies depending on the branch environment. We conclude that a modern, mildly arousing and pleasure-oriented retail environment is the most suited at maximizing customers approach behavior. Adverse effects from a highly-arousing environment are discussed in the light of the financial services context. Theoretical and managerial implications along with avenues for future research are proposed.